EVALUASI PROGRAM BEDAH RUMAH DALAM UPAYA PENGENTASAN KEMISKINAN DI DESA BERANGBANG, KECAMATAN NEGARA, JEMBRANA - Maha Dewi, Ni Kadek Sriyanti; Yudartha, I Putu Dharmanu; Prabawati, Ni Putu Anik (CITIZEN CHARTER, 2021)
The house renovation program in Berangbang Village is a government policy in helping the fulfilment of livable houses for the underprivileged. The purpose of this study was to evaluate the role of the house renovation program from 2017 tol 2019 in alleviating poverty in Berangbang Village. This research is using descriptive qualitative technique. While the data collection techniques in this research are observation, interviews, and documentation, using data analysis technique from Miles and Huberman. The evaluation model used in this research is by William Dunn (2003), which consists of six indicators, there are effectiveness, efficiency, adequacy, equality, responsiveness, and accuracy. The results in this study indicate that the role of the house renovation program in Berangbang Village is still not optimal, seen from the ineffective in alleviating poverty, insufficient budget, and inadequately targeted assistance. However, the government has made various efforts to optimize the implementation of the house renovation program. Keywords: Evaluation, House Renovation Program, Livable House, Poverty